2020
DOI: 10.15294/jpii.v9i4.24908
|View full text |Cite
|
Sign up to set email alerts
|

Sediments Quality based on Geo-Accumulation Index in Heavy Metals (Pb, Cu, and Cd) of Cengkok Coastal Waters, Banten Bay

Abstract: This area, which is located near the Banten Bay, is quite active with anthropogenic activities such as industry, fisheries, settlements, and shipyards that have the potential to pollute the environment with heavy metals. This study aims to determine the chemical environmental conditions of the waters and the concentration of heavy metals in the sediments of Banten Bay. Sediment samples were taken at five stations consisting of river and bay sections in April, May, July, August, and September 2019. Heavy metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
1
19
1
1
Order By: Relevance
“…Activities that affect heavy metals in waters are ship transportation, oil refinery industry activities, and coal industry [27]. In addition, copper metal (Cu) comes from residential waste, namely metabolic waste and pipe corrosion [28].…”
Section: Discussionmentioning
confidence: 99%
“…Activities that affect heavy metals in waters are ship transportation, oil refinery industry activities, and coal industry [27]. In addition, copper metal (Cu) comes from residential waste, namely metabolic waste and pipe corrosion [28].…”
Section: Discussionmentioning
confidence: 99%
“…Wardani et al (2020) stated that heavy metals are transported by currents where the flow conditions differ in strength in accordance with the season. 55 Wisha et al (2018) and Hamuna and Tanjung (2021) stated that the distribution of heavy metals in the sea is influenced by several water inputs and dynamics, topography, wind patterns, movement and surface current circulation. 56,57…”
Section: Heavy Metals In Sediment Samplesmentioning
confidence: 99%
“…The bioconcentration factors were low (<100) and still suitable for consumption by the local community as long as it does not exceed the safety level. Several studies related to waters in Banten Bay have also been investigated, including on the Cengkok coastal waters showed that the heavy metal concentration in the sediment has no significant effect on the environment and it is below the threshold (Wardani et al, 2020); and concentration of heavy metals in the Bojonegara coastal waters are still in a good condition for aquatic life (Surbakti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%